Assessing the benefits of gamification in mathematics for student gameful experience and gaming motivation. (July 2023) - Alt, Dorit
Abstract: This study addresses the question of how to use game design elements to raise students' motivation to engage in mathematics learning activities. Four conditions of mathematics learning activities were designed and assessed: 1. a problem-based digital gamification activity (research group 1); 2. a non-problem-based digital gamification activity (research group 2); 3. face-to-face game-based learning with a problem-based activity (control group 1), and 4. face-to-face game-based learning with a non-problem-based activity (control group 2). The effectiveness of the conditions was assessed in relation to the following dependent variables: (1) Gameful experience, including playfulness, challenge, accomplishment, and immersion; and (2) Gaming motivation, comprised of intrinsic and extrinsic motivation to play. A total of 779 students participated in this study from six Israeli public schools located in urban northern regions with similar socioeconomic profiles. The results mainly showed the superiority of the problem-based gamification activity compared to the other activities, in enhancing students' gameful experience and gaming motivation. The lowest results were obtained for the face-to-face game-based learning with a non-problem-based activity. These results mainly indicate that merely using gamification might not motivate students to actively participate in the learning activity unless it hinges on a sound pedagogical rationale. Highlights: Effect of four gamified activities on game experience and motivation was checked. A total of 779 students participated in this study from six Israeli public schools. Gamification utilizing problems in mathematics was found the most beneficial. The second effective activity was the non-problem-based gamification activity. The lowest results were shown for the F2F gamified non-problem-based activity.